DAMPAK PENDIDIKAN TERHADAP STRATIFIKASI SOSIAL DI DESA JUJUN KECAMATAN KELILING DANAU KABUPATEN KERINCI - ALSUNAH, M DHANY (journal of RESIDU, 2018)
ABSTRACT  This research is based on the condition and indication of the change of view or paradigm in the society of Jujun Village, Keriling Lake District, in view of the status and stratification of a person in relation to the level of education. This study aims to see how the impact caused by education on social stratification in Jujun Village Keriling District Lake Kerinci Province Jambi Province. This research type is qualitative research with descriptive method. This research is located in Jujun Village, Surrounding Lake Kerinci District, Jambi Province. Informants in this study are community leaders, Civil Servants and villagers JujunKecamatan Keliling Lake Kerinci District Jambi Province. Data were collected by interview and documentation study. The data were analyzed by data reduction, data presentation, and conclusion from the existing data to obtain the perfect data. The results show that education occupying the upper social layers in Jujun Village society and education greatly impacts social stratification in Jujun Village, because for previously uneducated community members, it is not so valued and respected in society. However, when he is able to complete his education to college and obtain a bachelor's degree he will be able to be in the upper social class, even though his family background is of the lower class. So that cause education in Jujun Village society is increasing. Based on the results of this study it can be concluded that education has an impact on social stratification in Jujun Village, Keriling Lake District. In Jujun Village society, education is seen as a way to be respected and respected so as to gain a better position and be in the upper social class in society . It is suggested to the community to be able to maintain their paradigm in viewing education and related parties such as Jujun Village government is expected to provide support for the progress of education in Jujun Village itself. Especially to members of the community from the lower classes if they want to send their children to school. Keywords: education, stratification and community